Agricultural technologies for climate change in developing countries: Policy options for innovation and technology diffusion - Lybbert, Travis J.; Sumner, Daniel A. (Food policy, 2012)
► Technology diffusion will shape how and how well farmers respond to climate change. ► We discuss relevant technologies and explore needed policies and institutions. ► Policies and institutions should reflect innovation, transfer and access considerations. ► Six policy principles emphasize information, incentives, flexibility, and trade inter alia. ► Policy priorities include market integration and public research support and capacity. Climate has obvious direct effects on agricultural production. The reverse is more apparent than ever as greenhouse gas emissions from agriculture are tallied. The development and effective diffusion of new agricultural practices and technologies will largely shape how and how well farmers mitigate and adapt to climate change. This adaptation and mitigation potential is nowhere more pronounced than in developing countries where agricultural productivity remains low; poverty, vulnerability and food insecurity remain high; and the direct effects of climate change are expected to be especially harsh. Creating the necessary agricultural technologies and harnessing them to enable developing countries to adapt their agricultural systems to changing climate will require innovations in policy and institutions as well. Potential constraints to innovation involve both the private and public sectors in both developing and developed countries. The process of transferring agricultural innovations across agroecological and climatic zones is often subject to agronomic constraints. Often, the most binding constraints occur at the adoption stage, with several factors that potentially impede poor farmers’ access to and use of new technologies. Based on discussions of these constraints, we derive six policy principles and use these principles to suggest several specific investments and policy priorities.